Safe Delivery Practices: Experience From Cross-sectional Data of Bangladeshi Women. (March 2015) - Kabir, M.A.; Goh, Kim-Leng; Khan, M.M.H.; Al-Amin, Abul Quasem; Azam, Mohammad Nurul
This study examines the safe delivery practices of Bangladeshi women using data on 4905 ever-married women aged 15 to 49 years from the 2007 Bangladesh Demographic and Health Survey. Variables that included age, region of origin, education level of respondent and spouse, residence, working status, religion, involvement in NGOs, mass media exposure, and wealth index were analyzed to find correlates of safe delivery practices. More than 80% of the deliveries took place at home, and only 18% were under safe and hygienic conditions. The likelihood of safe deliveries was significantly lower among younger and older mothers than middle-aged mothers and higher among educated mothers and those living in urban areas. Economically better-off mothers and those with greater exposure to mass media had a significantly higher incidence of safe delivery practices. A significant association with religion and safe delivery practices was revealed. Demographic, socioeconomic, cultural, and programmatic factors that are strongly associated with safe delivery practices should be considered in the formulation of reproductive health policy.